Answers

2014-08-29T09:29:28+08:00
4n-2=6w-12

tranpose -2 to the other side and change its sign to positive then simplify
4n=6w-10
 n=6w-10/4
n=6w- 2.6 ( for n )

4n-2=6w-10
 4n+8=6w
4n+8/6=w
4n+4/3=w

that is my answer







0
2014-08-31T19:23:25+08:00
Simplifying 4n + -2 = 6w + -12 Reorder the terms: -2 + 4n = 6w + -12 Reorder the terms: -2 + 4n = -12 + 6w Solving -2 + 4n = -12 + 6w Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4n = -12 + 2 + 6w Combine like terms: -2 + 2 = 0 0 + 4n = -12 + 2 + 6w 4n = -12 + 2 + 6w Combine like terms: -12 + 2 = -10 4n = -10 + 6w Divide each side by '4'. n = -2.5 + 1.5w Simplifying n = -2.5 + 1.5w
0